THE GENERATIVE THEORY OF SOCIAL COHESION AND CIVIC INTEGRATION - Mauro Giardiello (European Scientific Journal, ESJ, 2014)
The aim of this article is to develop a generative theory of social cohesion and civic integration in order to show the negative or positive impact on the processes of social and civic dissolution (crisis of values, participation and tolerance), that characterize the local realities (communities, neighborhoods,...). In the paper a conceptual clarification of both social cohesion and civic integration is developed away from theoretical, macro and especially a-contextual positions, lacking in a thorough analysis of those generative or degenerative processes triggered by local stakeholders to produce social reality. In line with these critical reflections Lockwood’s and Erikson’s approaches have been applied as they have been considered the most fruitful for the study at a micro level and for a possible revision based on the application of the category of social generativity and public space.